Eksekusi Jaminan Gadai Emas pada Bank Syariah Indonesia - Agus Setyawan; Sugeng Djatmiko (Syntax Corporation, 2023)
Pawn transactions in Islamic jurisprudence are called al rahn. Rahn has many definitions, one of which in Arabic rahn has a permanent and continuous meaning. As for the definition of rahn in sharia terms, the scholars explained with the phrase,